Financial Technology and Bank Profitability: Ghanaian Evidence - Prince Kofi Ofosu (Journal of Economics, Bussiness and Management Issues, 2025)
Fintech is a contemporary phenomenon that is revolutionizing the banking sector by introducing innovations that increase efficiency and streamline financial procedures. This paper explores the relationship between fintech and profitability of selected banks in Ghana from 2014 to 2023. Specifically, the research objectives are to analyze the impact of fintech on bank profitability and liquidity. A quantitative and explanatory study design were adopted. With 150 observations, the study utilized secondary data sourced from the annual financial reports of the selected banks and the World Bank Indicators Database. To assess the impact of fintech on bank profitability and liquidity, the OLS estimation method was utilized. The findings of the study offer a 2-way relationship between the variables. It was revealed that ATM banking has a positive impact on both bank profitability and liquidity. Findings of the study further revealed that Internet banking has a negative impact on profitability, but a positive impact on liquidity. In addition, it was found that mobile banking has a negative and positive impact on profitability and liquidity respectively. The study recommends that banks in Ghana should prioritize financial innovation, reduce transaction costs, and increase their security measures. This study concludes that fintech adoption plays a significant role in enhancing the profitability and liquidity creation of banks.